A Case for Culturo-Techno-Contextual Approach for Enhanced Academic Achievement in STEM Education - Hakeem Akintoye; Umar Ayotunde Adam; Soladoye Nurudeen Lameed; Isaac Sewanu Bankole; Benjamin Ayodeji (Universitas Riau, 2023)
The urgency to develop culturally and contextually responsive pedagogies in science education has become increasingly evident in recent times. In response, various teaching methods have been explored, showing successes in acquiring scientific knowledge. However, a more transformative approach is needed to fulfil the vision of the